PREPARATION OF THIN SEMICONDUCTOR FILMS AND THEIR ELECTRICAL PROPERTIES - B. Sapaev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
Using the SILD (layer-by-layer ion deposition) method, thin semiconductor films of tin oxosulfide with a thickness from 100 nm to 1 μm were obtained by varying the number of layering cycles from 10 to 100. The extreme nature of the influence of the number of layering cycles on the thickness, chemical composition and structural features of the resulting films was recorded. It has been shown that films with a thickness of about 1 micron consist of particles ranging in size from 70 nm to 300 nm.